2023
DOI: 10.3390/ijms24076647
|View full text |Cite
|
Sign up to set email alerts
|

Salinity-Triggered Responses in Plant Apical Meristems for Developmental Plasticity

Abstract: Salt stress severely affects plant growth and development. The plant growth and development of a sessile organism are continuously regulated and reformed in response to surrounding environmental stress stimuli, including salinity. In plants, postembryonic development is derived mainly from primary apical meristems of shoots and roots. Therefore, to understand plant tolerance and adaptation under salt stress conditions, it is essential to determine the stress response mechanisms related to growth and developmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 80 publications
0
4
0
Order By: Relevance
“…This complex interplay inevitably influences the rate of cell division, cell expansion, and cell wall formation [56]. Furthermore, salt-induced alterations affect the hormonal balance of roots and have other effects on root development [4]. The effects of salinity reduced the rate of cell division also include chromatin condensation, damage to the nuclear membrane, cytoskeleton disruption, ROS production in the meristem [59,62].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This complex interplay inevitably influences the rate of cell division, cell expansion, and cell wall formation [56]. Furthermore, salt-induced alterations affect the hormonal balance of roots and have other effects on root development [4]. The effects of salinity reduced the rate of cell division also include chromatin condensation, damage to the nuclear membrane, cytoskeleton disruption, ROS production in the meristem [59,62].…”
Section: Discussionmentioning
confidence: 99%
“…The decline in plant yield is intricately connected to the negative influence of salt on growth and developmental processes [1,4]. It is known that salinity adversely affects essential physiological processes, such as photosynthesis, transpiration, and uptake of water and essential mineral elements [1,5,6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This multifaceted receptor-like kinase GSO1 -mediated mechanism is pivotal in preserving intracellular ion homeostasis and, by extension, normal root development, thereby enabling roots to sustain growth in adverse environments ( Chen et al., 2023 ). Concurrently, it is imperative to recognize that the resilience and adaptability of plant apical meristem cells to salt stress are inextricably linked with microRNAs, the redox state, ROS, NO, and plant hormones such as auxin and cytokinin ( Yang and Lee, 2023 ). Recent research has found that a prion-like domain (PrD) in the key shoot meristem regulator STM can stimulate it to form nuclear condensates which are required for maintaining the shoot meristem.…”
Section: Mechanisms Governing Plant Stem Cell Responses To Abiotic St...mentioning
confidence: 99%
“…A comprehensive metabolome and transcriptome analysis of three CK signal-deficient Arabidopsis ahp2,3,5 and arr1,10,12 mutants treated with salt stress showed that CK signaling induced reprogramming of gene-metabolic networks associated with Arabidopsis response to salinity ( Abdelrahman et al., 2021 ). This intricate nexus highlights the correlation between salt stress response and signaling cascades that govern stem cell homeostasis in the plant meristem ( Yang and Lee, 2023 ).…”
Section: Mechanisms Governing Plant Stem Cell Responses To Abiotic St...mentioning
confidence: 99%